THE ESSENCE OF THE CONTENT AND STAGES OF DEVELOPMENT OF ACMEOLOGY - Qo‘ldoshev Rustambek Avezmuratovich (Modern American Journals, 2025)
This article provides information about the concept of acmeology, acmeological factors, main criteria, and also considers in detail the stages of the development of acmeology in the XX century. The presented data serve to introduce acmeology to the science of acmeology, to deepen the understanding of its content and essence.
Keywords: acmeology, person, personality, maturity, factor, professionalism, methodology, fundamentality, acmeological concept, acmeological factor.